Correlation of Delayed Onset Muscle Soreness and Inflammation Post-exercise Induced Muscle Damage - Sulistyarto, Soni; Irawan, Roy; Kumaat, Noortje Anita; Rimawati, Nanda (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Delayed Onset Muscle Soreness (DOMS) is a common injury resulting from abnormal intensive training in athletes, mainly the result of training involving eccentric contractions. AIM: The aim of this study was to determine the correlation between the incidence of DOMS and HMGB1 as a marker of the occurrence of inflammation post Exercise Induces Muscle Damaged. METHOD: 28 male recreational students of Sports Science Department, Universitas Negeri Surabaya who met all inclusion and exclusion criteria participated in this study. Participants completed a muscle damaging exercise which consists of a 10x10 drop jump (DRP) and a bout of 40×15 m sprints with a 5 m deceleration zone (SPR) to obtain a muscle damage effect. In this study, the stretching in the exercise session was not given, this was done to get the DOMS effect after exercise. DOMS and HMGB1 was carry out 1 hour before the exercise, 12 hours after the exercise, 24 hours after the exercise and 48 hours after the exercise. RESULT: The result showed that there was a significant correlation (r=0.935, p<0.05) between DOMS and HMGB1 as a predictor of inflammation. The participants that were given EIMD eccentric exercise (DRP and SPR) showed the occurrence of DOMS and increasing of HMGB1. The result also showed that there was a correlation between DOMS and HMGB1. CONCLUSION: This study concluded that there was a correlation between DOMS and HMGB1 as a marker of inflammation as the result of the eccentric exercise of the exercise Induced Muscle Damage (EIMD).